Ion bulk speeds and temperatures in the diamagnetic cavity of comet 67P from RPC-ICA measurements. Issue 2 (27th February 2021) - Bergman, Sofia; Stenberg Wieser, Gabriella; Wieser, Martin; Johansson, Fredrik Leffe; Vigren, Erik; Nilsson, Hans; Nemeth, Zoltan; Eriksson, Anders; Williamson, Hayley
ABSTRACT: Comets are constantly interacting with the solar wind. When the comet activity is high enough, this leads to the creation of a magnetic field free region around the nucleus known as the diamagnetic cavity. It has been suggested that the ion-neutral drag force is balancing the magnetic pressure at the cavity boundary, but after the visit of Rosetta to comet 67P/Churyumov–Gerasimenko the coupling between ions and neutrals inside the cavity has been debated, at least for moderately active comets. In this study, we use data from the ion composition analyser to determine the bulk speeds and temperatures of the low-energy ions in the diamagnetic cavity of comet 67P. The low-energy ions are affected by the negative spacecraft potential, and we use the Spacecraft Plasma Interaction Software to model the resulting influence on the detected energy spectra. We find bulk speeds of 5–10 km s −1 with a most probable speed of 7 km s −1, significantly above the velocity of the neutral particles. This indicates that the collisional coupling between ions and neutrals is not strong enough to keep the ions at the same speed as the neutrals inside the cavity. The temperatures are in the range 0.7–1.6 eV, with a peak probability at 1.0 eV. We attribute the major part of the temperature to the fact that ions are born at different locations in the coma, and hence are accelerated over different distances before reaching the spacecraft.